A Circularly Polarized Broadside Radiating “Herringbone” Array Design With the Leaky-Wave Approach - Cameron, T.; Sutinjo, Adrian; Okoniewski, M. (Institute of Electrical and Electronics Engineers, 2010)
A series-fed “herringbone” microstrip traveling wavecircularly polarized antenna array is designed to achieve broadsideradiation. It is shown that such an antenna can be modeledas a periodic leaky-wave (LW) structure, providing insight into radiationcharacteristics of interest, such as the directivity and beamangle of the structure, particularly at broadside. Full-wave simulationsas well as a prototype of the design verified the approach. Theextracted leaky-wave number properly predicts the behavior seenin radiation measurements, and no degradation in antenna gain isseen at or near broadside.